A Contribution on some Plants from Champaran District, North Bihar - Thothathri, K. (Indian Forester, 1965)
Critic al notes on Eulophia graminea Lindl., Leucas helicterifolia Haines, Ludwigia proslrala Roxb., Adhatoda liasica Nees., Hemigraphis hirta Anders. and Najas marina Linn. collected from the Champar an district, North Bihar are presented in this paper.